Short-Term L-Citrulline Supplementation Does Not Affect Blood Pressure, Pulse Wave Reflection, or Arterial Stiffness at Rest and during Isometric Exercise in Older Males - Andrea Tryfonos; Filippos Christodoulou; George M. Pamboris; Stephanos Christodoulides; Anastasios A. Theodorou (MDPI AG, 2023)
Hypertension and arterial stiffness are significant factors contributing to cardiovascular disease. L-citrulline, a nitric oxide precursor, has been proposed as a nutritional, non-pharmacological blood pressure-lowering intervention. This study aimed to investigate the impact of L-citrulline on central and peripheral blood pressure, pulse wave reflection, and central arterial stiffness at rest and during an isometric knee extension exercise protocol. Twelve older males received 6 g of L-citrulline or a placebo for six days using a double-blind crossover design. Blood hemodynamics parameters (i.e., aortic and brachial systolic and diastolic blood pressure, mean arterial pressure, pulse pressure, heart rate), pulse wave reflection (i.e., augmented pressure, augmentation index, forward/backward wave pressure), and arterial stiffness (i.e., carotid-femoral pulse wave velocity) were measured at baseline, post-supplementation, and during isometric exercise. No significant effects of L-citrulline supplementation were observed at rest or during exercise on blood pressure, pulse wave reflection, or arterial stiffness. Both central and peripheral blood pressure were increased during the exercise, which is consistent with isometric contractions. The results of the present study do not support any blood pressure-lowering effect of short-term L-citrulline at rest or during low-intensity isometric exercise compared to the pre-exercise values in older males.